2014
DOI: 10.1186/1745-6215-15-117
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pamidronate in Modic type 1 changes: study protocol for a prospective randomized controlled clinical trial

Abstract: BackgroundErosive degenerative disc disease, also known as Modic type 1 changes, is usually characterized by low back pain with an inflammatory pain pattern, as seen in spondyloarthropathies. Intravenous pamidronate has proven to be effective in patients with ankylosing spondylitis who are refractory to nonsteroidal antiinflammatory drugs, and in painful bone diseases in general, such as Paget’s disease, fibrous dysplasia or vertebral fractures. We therefore hypothesize that pamidronate would be effective in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Results of an open study seem to be encouraging52; a randomised controlled trial of 5 mg zoledronic acid found a significant improvement in LBP at 1 month,53 and a randomised controlled trial of 90 mg pamidronate, for 2 days consecutively, is ongoing 54. Other therapeutic options targeting bone marrow oedema such as surgical decompression or the prostaglandin analogue iloprost have not been assessed yet.…”
Section: Evolutionmentioning
confidence: 99%
“…Results of an open study seem to be encouraging52; a randomised controlled trial of 5 mg zoledronic acid found a significant improvement in LBP at 1 month,53 and a randomised controlled trial of 90 mg pamidronate, for 2 days consecutively, is ongoing 54. Other therapeutic options targeting bone marrow oedema such as surgical decompression or the prostaglandin analogue iloprost have not been assessed yet.…”
Section: Evolutionmentioning
confidence: 99%
“…Fourteen out of 40 (35%) patients did not meet AxSpA criteria, and IBP could be explained by another cause: 100% had Degenerative Disc Disease (DDD). Although DDD tends to present with chronic mechanic lumbar pain, Modic I disc diseases may manifest with IBP characteristics [33,34]. In addition, DDD is most frequently found in older patients, not associated to acute phase reactant changes.…”
Section: Discussionmentioning
confidence: 99%